2009
DOI: 10.3892/ijo_00000320
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in human lung carcinoma cells by the water extract of Panax notoginseng is associated with the activation of caspase-3 through downregulation of Akt

Abstract: Abstract. The root of Panax notoginseng is highly valued and commonly used in Oriental medicine. Although recent experimental data have revealed the proapoptotic potency of P. notoginseng extracts, the underlying molecular mechanisms of this apoptotic activity have not yet been studied in detail. In the present study, the effects of the water extract of P. notoginseng (WEPN) on the growth of human lung carcinoma cells were investigated. It was found that the exposure of A549 and NIC-H460 cells to WEPN resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A previous study reported that application of P. ginseng extract could induce apoptosis in A549 cells by activating p53 and caspase 3. 26 Changes in the expression of p53 correlated with changes in 2 downstream Bcl2 family proteins; BAX and Bcl2. This observation is in agreement with the transcriptional expression change of p53 in the A549 cell line.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study reported that application of P. ginseng extract could induce apoptosis in A549 cells by activating p53 and caspase 3. 26 Changes in the expression of p53 correlated with changes in 2 downstream Bcl2 family proteins; BAX and Bcl2. This observation is in agreement with the transcriptional expression change of p53 in the A549 cell line.…”
Section: Discussionmentioning
confidence: 97%
“…Elevated LY-6K is a serologic diagnostic biomarker and therapeutic target for breast cancer, lung and esophageal carcinomas, bladder cancer, and esophageal squamous cell carcinoma (ESCC) (28-31). Induced LY-6K regulates cell growth, invasion, and migration of lung, esophageal, breast, and bladder cancer cell lines (29,30,32). Additionally, LY-6K is an immunotherapeutic target of cancer vaccine therapies because LY-6K stimulates cytotoxic T lymphocytes that have specific cytotoxic activity against ESCC cells that endogenously express LY-6K (33).…”
Section: Functional Analysis Of Ly-6/upar Moleculesmentioning
confidence: 99%